Teaching Phonics and Vocabulary Through Children’s Literature in Early Childhood Initial Teacher Education: Trial of the Non-Scripted Intentional Teaching (N-SIT) Tool - Stacey Campbell; Michelle M. Neumann; Lesley Friend (Education Sciences, 2025)
Current policy recommendations for initial teacher education encourage teaching code-related literacy (phonics, phonological awareness, and phonemic awareness) over pedagogical knowledge, and engaging practice in learning to read. To enhance early childhood pre-service teacher (PST) practices, this mixed-methods pilot study investigated a tool to support PSTs studying birth-to-eight years teaching, pedagogical practice, and knowledge to teach code-related literacy and supplementary vocabulary in conjunction with quality children’s literature. The Non-Scripted Intentional Teaching (N-SIT) tool was developed and then trialled with early childhood PSTs (n = 24) in Queensland, Australia. The participants planned phonics learning experiences using the N-SIT and picture books (e.g., Pig the Pug; Snail and the Whale). Survey data gathered participants’ code-related literacy knowledge before and after the N-SIT training. The data revealed most PSTs felt well-to-somewhat prepared to teach beginning reading and vocabulary and less-to-somewhat prepared to teach phonics. The data further revealed that all participants could define phonics but reported mixed conceptual understandings of phonological and phonemic awareness. The PSTs’ knowledge of phonological awareness, phonemic awareness, and planning for phonics-focused teaching through children’s literature improved post-N-SIT activity. Planned direct systematic phonics instruction strategies through the intentional shared reading of children’s literature and the potential benefits of the N-SIT tool in early childhood initial teacher education are discussed.